TINGKAT KEMAMPUAN GERAK (MOTOR ABILITY) DENGAN HASIL BELAJAR PENJAS SISWA SD NEGERI 04 SITIUNG KECAMATAN SITIUNG KABUPATEN DHARMASRAYA - Mahlizar Mahlizar (Dharmas Journal of Sport, 2021)
This study aims as teaching material for lecturers of Penjaskesrek, Dharmas University Indonesia. In general, the purpose of this research and development is to produce learning exercises for basic soccer passing techniques. This type of research is development research using the Research and Development (R&D) development exercise from Borg and all. Research location at Dharmas Indonesia University, Dharmasraya Regency, West Sumatra. The instruments in this research and development are questionnaires, questionnaires, as well as basic soccer passing technical test instruments used to collect data at the following stages: (1) needs analysis; (2) expert evaluation (initial product evaluation); (3) limited trials (small group trials); and (4) field testing. Based on the results of small group trials carried out on 10 basic soccer passing technique learning exercises, by experts the use of the whole exercise in this development can be categorized as valid and suitable for use in the development of soccer passing practice for students of Penjaskesrek, Dharmas University Indonesia. After the results of the development of basic passing technique exercises were tested on a small scale and were revised, the next step was to conduct large group trials.